The Arden Shakespeare miscellany - Armstrong, Jane (Arden Shakespeare/Methuen Drama, 2011)
A gem of a reference book covering everything you could possibly want to know about Shakespeare between two handsome covers. Entries are quite short and range from ""What did Shakespeare look like?"", ""Shakespeare on Film"" and lists of compliments, oathes, lovers'' vows and boys and girls names. There is an entry for each play too, summarising its plot and outlining major characters and themes. Details are given of the debates surrounding Shakespeare''s identity, the known and fanciful facts of his life, and descriptions of the theatres in which he worked and the acting companies of which he.